Learning Model Problem Based Learning Improve learning outcomes Indonesian Language Lesson Content. - Wahyu Handayani (Universitas Sebelas Maret, 2022)
The low learning outcomes of students' Indonesian lesson content are due to less innovative learning models and a lack of linkages between learning material and real life. The purpose of this study was to analyze the Problem Based Learning learning model for learning outcomes of Indonesian language content in class V students. The method used is a classroom action research. Each meeting is carried out pre-test and post-test to determine the progress of students. The results showed that the Problem Based Learning learning model could improve the learning outcomes of Indonesian language content for fifth grade students. This was evidenced from student learning outcomes in the pre-cycle with an average score of 54.5 which was in the low category, cycle I with an average score -an average of 63.3 which is in the sufficient category and in cycle II the average increase is 80.2 in the high category.